2005
DOI: 10.1080/10236190500386275
|View full text |Cite
|
Sign up to set email alerts
|

Population models with periodic recruitment functions and survival rates

Abstract: We study the combined effects of periodically varying carrying capacity and survivalrate on populations. We showthat our populations with constant recruitment functions do not experience either resonance or attenuance when either only the carrying capacity or the survivalrate is fluctuating. However,when both carrying capacity and survivalr ate are fluctuatingt he populations experience either attenuance or resonance, depending on parameter regimes. In addition, we showthat our populations with BevertonHolt re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…If one assumes that γ n = γ is constant in (1.2), then it may be shown that the same result holds, that is, (1.2) is attenuant in the mean. However, if both parameters γ n and K n are random sequences, we are still unable to determine either attenuance in the mean or resonance in the mean, that is for almost every ω ∈ Ω and every x ∈ R + , The problem of attenuance or resonance has not been yet resolved even when γ n and K n are periodic sequences on Z + , (see for example Elaydi-Sacker [3], and FrankeYakubu [4]). It would be of great interest to develop criteria for attenuance and resonance for the case of two varying parameters Beverton-Holt equation with a survival rate.…”
Section: Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…If one assumes that γ n = γ is constant in (1.2), then it may be shown that the same result holds, that is, (1.2) is attenuant in the mean. However, if both parameters γ n and K n are random sequences, we are still unable to determine either attenuance in the mean or resonance in the mean, that is for almost every ω ∈ Ω and every x ∈ R + , The problem of attenuance or resonance has not been yet resolved even when γ n and K n are periodic sequences on Z + , (see for example Elaydi-Sacker [3], and FrankeYakubu [4]). It would be of great interest to develop criteria for attenuance and resonance for the case of two varying parameters Beverton-Holt equation with a survival rate.…”
Section: Remarksmentioning
confidence: 99%
“…In a recent paper, Franke and Yakubu [4] studied (3.2) with the periodic constant recruitment function…”
Section: Mean Almost Periodicity Of the Solutionmentioning
confidence: 99%
“…Jillson performed such an experiment with laboratory cultures of Tribolium [34]. Others have used mathematical models to study the effects of periodic forcing on population dynamics [8,9,10], [12,13,14,15,16,17], [20,21,22,23,24], [29,30], and [35,36,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…The ecological literature is filled with future life-history studies of periodically forced (nonautonomous) classical parametric population models with time t in Z + . Examples of such periodically forced parametric models with time t in Z + include the Beverton-Holt, Ricker, Smith-Slatkin and LPA models [9,10], [13,14,15,16], and [21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation